2009
DOI: 10.1007/s11573-009-0330-1
|View full text |Cite
|
Sign up to set email alerts
|

Prüfungshonorare in Deutschland – Determinanten und Implikationen

Abstract: Zusammenfassung: Die aufgrund der Verabschiedung des Bilanzrechtsreformgesetzes seit 2005 verfügbaren Honorare für Abschlussprüfungen belegen eine außerordentlich hohe Anbieterkonzentration auf dem deutschen Markt fürAbschlussprüfungen kapitalmarktorientierter Unternehmen. Damit liegt die Annahme von Wettbewerbsverzerrungen zulasten von Unternehmen und insbesondere von Honoraren oberhalb des Gleichgewichtspreises auf Polypolen nahe. Auf Basis einer multivariaten Regressionsanalyse, der eine für Deutschland bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
1
18
0
3
Order By: Relevance
“…As switches of a company's audit firm are likely to result in lower audit quality due to losses in client-specific knowledge (Chen, Lin, & Lin, 2008;Tanyi, Raghunandan, & Barua, 2010), as well as in reductions in the amount of audit fees paid (Deis & Giroux, 1996;Köhler, Marten, Ratzinger, & Wagner, 2010;Köhler & Ratzinger-Sakel, 2012), both models control for whether the incumbent auditor has audited the financial statements of the respective company in the previous year or not (Switch). Furthermore, both models control for whether the company is audited by a Big 4 audit firm or not (Big4), as many previous studies have demonstrated that Big 4 audit firms are likely to provide higher audit quality (e.g., Lin & Hwang, 2010) and to charge higher audit fees (e.g., Campa, 2013).…”
Section: Characteristics Related To the Audit Engagementmentioning
confidence: 99%
“…As switches of a company's audit firm are likely to result in lower audit quality due to losses in client-specific knowledge (Chen, Lin, & Lin, 2008;Tanyi, Raghunandan, & Barua, 2010), as well as in reductions in the amount of audit fees paid (Deis & Giroux, 1996;Köhler, Marten, Ratzinger, & Wagner, 2010;Köhler & Ratzinger-Sakel, 2012), both models control for whether the incumbent auditor has audited the financial statements of the respective company in the previous year or not (Switch). Furthermore, both models control for whether the company is audited by a Big 4 audit firm or not (Big4), as many previous studies have demonstrated that Big 4 audit firms are likely to provide higher audit quality (e.g., Lin & Hwang, 2010) and to charge higher audit fees (e.g., Campa, 2013).…”
Section: Characteristics Related To the Audit Engagementmentioning
confidence: 99%
“…Besides a slight increase for the concentration ratio over time can be determined. Koehler et al (2010), Sattler (2011) and Quick and Sattler (2011) Since the first measurements, an overview manifests a high provider concentration on the German audit market and increasing development over the period of time as a permanent phenomenon, even for the last examined year 2007. On the German audit market, the supplier concentration can be classified as an oligopoly of the Big Four, where in certain industries or market segments even monopoly resp.…”
Section: Germanymentioning
confidence: 99%
“…For instance, in one of the first German empirical studies, Bigus and Zimmermann ) find insignificant results for initial audit fee discounts, whereas Köhler et al . () provide evidence supporting fee‐cutting practices by German audit firms. Further, Wild () provides mixed results for low‐balling discounts in Germany.…”
Section: Introductionmentioning
confidence: 85%